The global financial crisis and integration in European retail banking - Rughoo, Aarti; Sarantis, Nicholas (Journal of Banking & Finance, 2014)
The aim of this paper is twofold. Firstly, to investigate the integration process within the European Union retail banking sector by analysing deposit and lending rates to the household sector during the period 2003–2011. Secondly, to assess the impact of the 2008 global financial crisis on the banking integration process, an area that is yet unexplored. An important contribution of the paper is the application of the recently developed Phillips and Sul (2007a) panel convergence methodology which has not hitherto been employed in this area. This method analyses the degree as well as the speed of convergence, identifies the presence of club formation, and measures the behaviour of each country’s transition path relative to the panel average. The empirical results point to the presence of convergence in all deposit and lending rates to the household sector up to 2007. In sharp contrast, the null of convergence is rejected in all deposit and credit markets after the onset of the 2008 financial crisis. These results show that the global crisis has had a detrimental effect on the banking integration process. We find some convergence in a few sub-clusters of countries but the rate of convergence is typically slow and several countries are identified as diverging altogether. In addition, we find that the credit market, in general, is far more heterogeneous than the savings market.